2021
DOI: 10.1111/pere.12374
|View full text |Cite
|
Sign up to set email alerts
|

Can I trust you? Children's perceptions of friends and classmates who gossip

Abstract: This study examined children and adolescents' perceptions of trustworthiness about peers who shared gossip. Participants (N = 134, ages 8–16 years) completed vignettes from the gossip listener's perspective and evaluated how trustworthy the sharer was. The main findings revealed that a classmate gossiping negatively about the listener's friend was considered less trustworthy than the other relationship type conditions. Furthermore, in negative gossip scenarios, the sharer was rated more trustworthy when gossip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In studies of selective trust in testimony, children have been found to show a positivity bias, i.e., they endorse positive rather than negative claims (Boseovski, 2010). Moreover, as noted above, preschoolers rate a positive gossiper more highly than a negative gossiper (Ruggiero et al, 2020; Shinohara & Kobayashi, 2022), and 8‐ to 10‐year‐old children regard children who share negative gossip as less trustworthy than children who share positive gossip (Caivano et al, 2021). Based on children's positivity bias (Boseovski, 2010), and on the increase with age in that bias (Boseovski et al, 2017), we anticipated that children would trust an individual supplying positive rather than negative gossip and believe the content of positive rather than negative gossip.…”
Section: Introductionmentioning
confidence: 91%
“…In studies of selective trust in testimony, children have been found to show a positivity bias, i.e., they endorse positive rather than negative claims (Boseovski, 2010). Moreover, as noted above, preschoolers rate a positive gossiper more highly than a negative gossiper (Ruggiero et al, 2020; Shinohara & Kobayashi, 2022), and 8‐ to 10‐year‐old children regard children who share negative gossip as less trustworthy than children who share positive gossip (Caivano et al, 2021). Based on children's positivity bias (Boseovski, 2010), and on the increase with age in that bias (Boseovski et al, 2017), we anticipated that children would trust an individual supplying positive rather than negative gossip and believe the content of positive rather than negative gossip.…”
Section: Introductionmentioning
confidence: 91%
“…Earlier studies that examined reactions to gossip have not yet measured motive interpretations. For example, Caivano and colleagues found that gossipers were rated as less trustworthy when sharing negative gossip, but this effect was moderated by the content of the information shared: gossipers were considered more trustworthy if the negatively‐valenced gossip involved more actors who were affected by “bad” behavior of the gossip target than just the gossiper (Caivano et al., 2021).…”
Section: Interpreting Gossip Motivesmentioning
confidence: 99%